Meta-analysis of the intervention effects of taekwondo on metabolic syndrome indicators - Han, Zhengfa; Ju, Hanyu (Frontiers in Physiology, 2023)
Objective: To quantify the effect of taekwondo as an intervention on the indicators of metabolic syndrome and identify an intervention plan with the optimal effects. Methods: Combining the Cnki.net, Wanfang, PubMed, Web of Science, Embase, KISS, RISS, and DBPIA databases, this paper retrieved relevant references in Chinese, English, and Korean, applied Review Manager 5.4 software to evaluate the methodological quality of the included references according to the Cochrane manual, and utilized Comprehensive Meta-Analysis version 3.7 to perform statistical analyses. Result: A total of 45 references and 1079 related subjects were included in the analysis. The results of the meta-analysis showed that taekwondo has a beneficial effect on all indicators of metabolic syndrome (Hedges’ g [effect size] = −0.615, −0.672, −0.497, −0.785, −0.591, and 0.435; p < 0.05). Subgroup analysis revealed the superior intervention effect of taekwondo on metabolic syndrome in women compared to men, middle-aged and elderly compared to other age groups, and abnormal metabolic syndrome indicators compared to normal values. Moreover, the best results were obtained for longer intervention durations—12 weeks—three times per week, for 40–50 min per session. In addition, the combination of intervention types (poomsae, kick, and taekwondo gymnastics) showed optimal effects. The exercise intensity should consider the characteristics of the intervention object and be generally set to medium or high intensity. Conclusion: Taekwondo can effectively improve metabolic syndrome, as evidenced by decreased body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood glucose (FBG), and triglyceride (TG) levels and increased high-density lipoprotein cholesterol (HDL-C) level. Taekwondo had the greatest effect on quinquagenarian women with abnormal levels of metabolic syndrome indicators. To maximize the intervention effect of taekwondo on metabolic syndrome, an exercise prescription of high-intensity poomsae, kick, and taekwondo gymnastics performed in 40–50 min sessions, three times weekly for 12 weeks is recommended.